Participation in ICT Development Interventions: Who and How?. Issue 1 (5th December 2017) - Thapa, Devinder; Sæbø, Øystein
Abstract: The aim of participatory development (PD) in the context of using Information and Communication Technologies (ICT) for development (ICT4D) is to empower underprivileged communities and disadvantaged segments of the stakeholders. The literature on ICT4D is replete with empirical evidence showing that ICT interventions often fail since they are often externally initiated, with very limited involvement from the affected (Heeks, 2002). Clearly, the principles and concepts of PD are relevant to ICT4D. However, we should not consider PD a panacea but need to understand the caveats and processes by which PD happens. Questions to ask include: What are the various challenges in PD? Who are the relevant stakeholders? Why and how do actors enrol in the project? How do we create sustainable ICT4D projects through PD? To understand these research questions, we present a case analysis of a project in Nepal called the Nepal Wireless Networking Project (NWNP). Investigating the specific initiatives that they enabled, telemedicine, education and jobs, we propose that the key participants in the NWNP were activist actors and the affected and that activists drew upon existing Social Capital to enrol the affected through a process explained by Actor Network Theory (ANT). In the process, they built other forms of Social Capital, which in turn extended the benefits of PD to several mountain villages.